Though all things differ: pluralism as a basis for cooperation in forests - Wollenberg, Eva Karoline; Anderson, J.; López, C. (Center for International Forestry Research, 2005)
Pluralism is a political belief that acknowledges individuals’ rights to pursue their interests, but requires society to resolve differences where they infringe upon each other. This guide shows how pluralism helps people to value social differences and provides clear principles and rules about how to coordinate those differences. The guide reviews pluralism’s origins, key elements and strengths and weaknesses. It examines how people think about differences, including the psychological obstacles that cause us to exclude or ignore others. Practices are examined with examples drawn from forest-related contexts: legal pluralism, multistakeholder processes and diversity in work teams. Questions are provided to help the reader assess and practice pluralism in their own settings. The guide concludes that understanding the political assumptions and principles of pluralism can enrich our understanding of current practices to develop fundamentally new approaches to forest decision-making.